2020
DOI: 10.1007/s10549-020-05856-3
|View full text |Cite
|
Sign up to set email alerts
|

Immune system and angiogenesis-related potential surrogate biomarkers of response to everolimus-based treatment in hormone receptor-positive breast cancer: an exploratory study

Abstract: Purpose mTOR inhibitor everolimus is used for hormone receptor-positive (HR+)/HER2-negative metastatic breast cancer (mBC). No reliable predictive biomarker of response is available. Following evidences from other solid tumors, we aimed to assess the association between treatment-associated immune system features and everolimus activity. Methods We retrospectively explored a correlation with the therapeutic activity of everolimus and tumor-associated immune pathways with ingenuity pathway analysis (IPA), neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(62 reference statements)
1
13
0
Order By: Relevance
“…2 e). In addition, genes related to angiogenesis have been reported to play essential roles in modulating the tumour microenvironment and the immune environment [ 36 ]. We calculated each sample's angiogenesis score and found that scores for the four groups were significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…2 e). In addition, genes related to angiogenesis have been reported to play essential roles in modulating the tumour microenvironment and the immune environment [ 36 ]. We calculated each sample's angiogenesis score and found that scores for the four groups were significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…Lymphocytes, whether in peripheral blood or as tumor-in ltrating lymphocytes, play a major role in controlling disease progression. For example, in patients receiving everolimus for mBC, Schettini et al reported that responders had a higher number of circulating CD8+ and CD4+ T cells, and increased pretreatment in ltration of these cells in the tumor microenvironment than non-responders [30].…”
Section: Discussionmentioning
confidence: 99%
“…62,63 Patients with a neutrophil to lymphocyte ratio below 4.4 had a superior PFS compared with patients with baseline neutrophil to lymphocyte ratio above 4.4 (Log Rank test p = 0.01). 62 Changes in Standardized Uptake Values (SUV) of Positron Emission Tomography (PET) scans at 3 months compared with baseline SUV were examined in a small study of 31 patients with metastatic ER positive, HER2 negative breast cancer receiving exemestane and everolimus. 64 A change of SUV by more than 28.8% was found to be an optimal cut-off to predict PFS at 10 months.…”
Section: Clinical Biomarkersmentioning
confidence: 96%
“…62 Data from a sub-set of patients from the phase IIIb trial mentioned in the previous paragraph disclosed that the neutrophil to lymphocyte ratio in peripheral blood was predictive of outcomes to treatment with exemestane and everolimus. 62,63 Patients with a neutrophil to lymphocyte ratio below 4.4 had a superior PFS compared with patients with baseline neutrophil to lymphocyte ratio above 4.4 (Log Rank test p = 0.01). 62 Changes in Standardized Uptake Values (SUV) of Positron Emission Tomography (PET) scans at 3 months compared with baseline SUV were examined in a small study of 31 patients with metastatic ER positive, HER2 negative breast cancer receiving exemestane and everolimus.…”
Section: Clinical Biomarkersmentioning
confidence: 99%